Antibodies against p53 protein in serum of patients with benign or malignant pancreatic and biliary diseases. Issue 3 (March 1995) - Laurent-Puig, P; Lubin, R; Semhoun-Ducloux, S; Pelletier, G; Fourre, C; Ducreux, M; Briantais, M J; Buffet, C; Soussi, T
Abstract : Specific markers for pancreatic or biliary cancer have been developed in the past few years. Ca 19-9 has a good sensitivity but it is also increased in benign cholestasis. Mutations in the p53 gene are commonly reported in pancreatic cancer and can be detected by a serological analysis. The aim of this work was to find out the sensitivity and specificity of this new assay in diagnosing cancer of the pancreas or of the bile ducts. The presence of antibodies against p53 was determined by an enzyme linked immunosorbent assay (ELISA) in 29 patients with pancreatic cancer, 33 with biliary tract cancer, and 33 with benign biliary or pancreatic diseases as controls. p53 Antibodies were detected in eight of 29 patients with pancreatic cancer (28%), in five of 33 patients with biliary tract (15%), and in one patient (3%) with stones of the common bile duct. The sensitivity and the specificity for the diagnosis of malignant biliary or pancreatic diseases were 21% and 96% respectively. It is concluded that the presence of p53 antibodies in the serum of patients with pancreatic and biliary diseases is specific for malignancy and independent from the presence of cholestatic disease.